Impact of Environmental and Climatic Factors on Animal Health and Livestock Population Dynamics in Al-Bayda, Libya - Warda awad (المجلة الدولية للنشر العلمي, 2026)
Semi-arid Mediterranean livestock systems sit at the meeting point of two pressures: a climate that is warming and drying, and rangelands already carrying more animals than they can comfortably support. This paper asks how those pressures translate into measurable consequences for animal health, productivity and herd dynamics in Al-Bayda and the surrounding Al-Jabal Al-Akhdar region of north-eastern Libya. A narrative synthesis was undertaken, drawing on peer-reviewed literature published between 2015 and 2026 alongside sectoral and institutional reporting for Libya and North Africa. Retrieved evidence was organised around five thematic drivers: thermal load, rainfall variability and drought, atmospheric humidity, vector ecology, and rangeland degradation. Compiled regional estimates place the inventory at approximately 940,500 head. Sheep dominate (520,000 head; 55.3%), followed by goats (265,000; 28.2%), cattle (78,000; 8.3%), poultry (56,000 birds; 5.9%) and camels (21,500; 2.3%) — small ruminants therefore account for more than four-fifths of the regional herd. Three constraints recur across the evidence base: heat load during the summer months, tick infestation and the haemoprotozoan infections that accompany it, and feed deficits driven by drought. Seasonal contraction of herd size is pronounced, with summer numbers falling roughly 10% below the winter baseline in sheep and cattle. Cattle emerge as the most exposed species, consistent with their higher water and nutrient demands, while small ruminants show greater tolerance of adverse conditions but lower absolute output. Because the quantitative material assembled here is secondary and partly estimated, the figures should be read as indicative of magnitude and direction rather than as validated measurements. On that basis, the paper argues for three priorities: a functioning veterinary surveillance system linked to climate data, grazing management that respects measured carrying capacity, and selection for heat-tolerant animals suited to eastern Libyan conditions